Моделювання НЕ-факторів — основа інтелектуалізації комп’ютерних технологій - Valkman, Yu. R.; Bykov, V. S.; Rykchalsky, A. Yu. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
Some problems of Non-factors modeling in computer systems are discussed. A brief review of related publications is given. The crucial role of Non-factors in creative thinking processes is shown. A three-dimensional classification of Non-factors is introduced. The main purpose of the paper is to argue for the necessity of Non-factors modeling in the development of advanced intelligent technologies of the ХХІ st century.